2020
DOI: 10.3164/jcbn.19-44
|View full text |Cite
|
Sign up to set email alerts
|

The effects of isoflavone supplementation plus combined exercise on salivary markers of oxidative stress in postmenopausal women

Abstract: This study tested the effect of isoflavone supplementation in addition to combined exercise training in salivary oxidative stress markers in non obese postmenopausal women. Thirty two post menopausal women without hormone therapy were randomly assigned to exercise + placebo (n = 15) or exercise + isoflavone supplementation (n = 17) groups. They performed 30 sessions of combined exercises (aerobic plus resistance) over ten weeks and consumed 100 mg of isoflavone supplementation or placebo. Saliva samples were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Data suggest that oxidative stress is involved in age-related diseases by destroying the antioxidant defense system. In the body's normal state, antioxidants apply detoxification mechanisms against reactive oxygen species (ROS) 27 . By aging, antioxidant levels remarkably decrease, and the body becomes more prone to complications such as menopause disturbances 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data suggest that oxidative stress is involved in age-related diseases by destroying the antioxidant defense system. In the body's normal state, antioxidants apply detoxification mechanisms against reactive oxygen species (ROS) 27 . By aging, antioxidant levels remarkably decrease, and the body becomes more prone to complications such as menopause disturbances 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In the body's normal state, antioxidants apply detoxification mechanisms against reactive oxygen species (ROS). 27 By aging, antioxidant levels remarkably decrease, and the body becomes more prone to complications such as menopause disturbances. 28 There are some shreds of evidence that claim overproduction of ROS due to estrogen decline in menopause women and also hypoestrogenism is considered as an important factor in attenuation of antioxidant defense capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant property of these substances may partly contribute to the effect of AGE on periodontitis as the importance of salivary protection for oxidative stress has been shown to keep the oral health conditions. (27,28) In addition to the antioxidant property, SAC, S1PC and SAMC have been shown to help improve the peripheral circulation, reduce inflammation, and enhance immunological potency, that may all contribute to the beneficial effect of AGE on periodontitis. (29)(30)(31)(32)(33) Most recently, Ohtani and Nishimura (34) showed that S1PC, SAC and SAMC act together to inhibit LPSinduced inflammation in human gingival epithelial cells in culture by suppressing intercellular adhesion molecule-1 expression and IL-6 secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, estrogen's capacities to prevent oxidative stress processes and to produce antioxidant molecules decrease in menopause [3]. Furthermore, the mechanisms involved in antioxidant protection deteriorate with age [4], with an adequate prooxidant-antioxidant balance being essential to maintaining healthy conditions for physiological activities [5].…”
mentioning
confidence: 99%